COVID-19 in Pregnancy: Implication on Platelets and Blood Indices - Nori, Wassan; Hameed, Ban Hadi; Thamir, Asmaa Rajih; Fadhil, Amenah (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective To describe the hematological changes, the platelet indices in particular, in pregnant women with coronavirus disease 2019 (COVID-19) compared to healthy pregnant women.Methods A retrospective case-control study conducted at the Al Yarmouk Teaching Hospital, in Baghdad, Iraq, involving 100 pregnant women, 50 with positive viral DNA for COVID-19 (case group), and 50 with negative results (control group); both groups were subjected to a thorough hematological evaluation.Results Among the main hematological variables analyzed, the platelet indices, namely the mean platelet volume (MPV) and the platelet distribution width (PDW), showed statistically significant differences (MPV: 10.87 ± 66.92 fL for the case group versus 9.84 ± 1.2 fL for the control group; PDW: 14.82 ± 3.18 fL for the case group versus 13.3 ± 2.16 fL for the controls). The criterion value of the receiver operating characteristic (ROC) curve for PDW at a cutoff point of > 11.8 fL showed a weak diagnostic marker, while the MPV at a cutoff value of > 10.17 fL showed a good diagnostic marker.Conclusion The MPV and PDW are significantly affected by the this viral infection, even in asymptomatic confirmed cases, and we recommend that both parameters be included in the diagnostic panel of this infection.
Keywords: COVID-19; pregnancy; platelet indices; mean platelet volume; platelet distribution width